Case Study : Hannan Medispa Jerteh / Nurul Syafiqah Shamsul Bahari - Shamsul Bahari, Nurul Syafiqah (2020)
With the utilization of SWOT analysis, I was able to figure out the strengths and weaknesses a company use their footholds. After I have perused the strengths and weakness, then only I can build upon that strength and work on that weakness to someday turn that weakness into leverage. As the saying goes, never underestimate your strength, never overestimate your weakness. Besides that, as I become aware of the opportunity and threat that enwreathe this line of business, I can better exploit this to either gain more mileage or to avoid some unwanted predicament that can drag us down. The line between opportunity and threat is thin since some opportunity maybe a threat, but every threat is an opportunity to learn something. I should always be vigilant and take a calculated risk if I am to thrive in the business world. Capitalizing on those worlds, technology development or improvement is always a risky move but it can be alleviated with a thorough analysis of the market and products/ services. With the up-to-date the technology of spa treatment and hair treatment, surely it can provide the best and comfortable services for the customers.